Analysis of power factor corrections for obtaining improved power factors of switching mode power supply - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2020)
This article discusses such an important issue as the power factor of Switching Mode Power Supply (SMPS) and its improvement through Power Factor Correction (PFC). The power factor shows how effectively uses the consumption of electric energy by certain loads connected to the power distribution system with Alternative Current (AC), which is very critical for the electricity-producing industry. The number of power factors is a dimensionless value that can vary from -1 to 1. Thus, in an electric power system, a load with a low power factor draws more current than a load with a high power factor for the same amount of transferring useful power, which may cause overloading of the power grid and lead to over-expenditure of electricity. Otherwise, designing power factor correction (PFC) into modern switched-mode power supplies (SMPS) has evolved over the past few years due to the introduction of many new controller integrated circuits (IC). Today, it is possible to design a variety of PFC circuits with different modes of operation, each with its own set of challenges. As the number of choices has increased, so has the complexity of making the choice and then executing the new design. In this article, the design considerations and details of operation for the most popular approaches are provided.Â Â